Testing for break-even effect in the indonesian capital market - Yohanis, Yohanis; Margaretha, Farah; Usman, Bahtiar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to find out whether investors experience a break-even effect. The research method used in this study was the Leal et al. (2017) method to find the break-even effect. The results show a break-even effect in several years, 2012 and 2015. This means that only in those two years did individual investors experience a break-even effect as indicated by the Proportion of Winners Additionally Purchased (PWAP), which was more significant than the Proportion of Losers Additionally Purchased (PLAP). The limitation of the research is that there are still several other methods that can be developed to find the break-even effect. Bullish and bearish market conditions are also expected to influence investors' decisions. The research implication for securities companies and capital market authorities is that it is necessary to support individual customers through education to avoid these two effects. Investors need to be aware of the break-even effect. Research on individual investors is still minimal. In addition, it uses a sample of secondary data from individual investor transactions to find the relatively new break-even effect on the Indonesia Stock Exchange.